Pengaruh Penggunaan Model Talking Stick Berbasis QR Code Terhadap Hasil Belajar IPAS Kelas IV SDN Gugus IX Kota Bengkulu - Mediana, Annisa; Amaliyah, Yuli (JURIDIKDAS, 2025)
This study aims to determine the effect of using the QR Code-based Talking Stick learning model on the learning outcomes of fourth grade students of SDN cluster 9 Bengkulu City. This research is a quantitative study using a pseudo-experimental method with (The Matching Only Pretest-Posttest Control Group Design). The population of this study were grade IV students of SDN in cluster 9 Bengkulu City which are accredited A, public elementary schools, and use the independent curriculum. The sample of this study consisted of two groups, namely class IVC SDN 82 Bengkulu City as the experimental group using the QR Code-based Talking Stick model and class IVA SDN 61 Bengkulu City as the control group using the conventional model. The results showed that the average of the experimental group and control group on the pretest was relatively the same, while the average on the posttest had a significant difference. The average on the control group posttest was 54,04 while the average on the experimental group posttest was 65,22. The results of the independent sample t-test on the pretest showed no significant difference between the two groups. While the results of the independent sample t-test test on the posttest showed that the tcount of 2,187 was greater than the ttable which was 2,011 (df = 48, α = 0,05) the value of Sig. (2-tailed) of 0,034 <0,05 which means there is a significant difference between the two groups.